Effects of Urban Green and Blue Space on the Diffusion Range of PM2.5 and PM10 Based on LCZ - Ruiyuan Jiang; Changkun Xie; Zihao Man; Rebecca Zhou; Shengquan Che (Land, 2023)
Urban green and blue space (GBS) significantly impacts the diffusion range of atmospheric particulate matter. By determining the diffusion distance of atmospheric particulate matter (PM2.5 and PM10) in Shanghai, combined with the GBS landscape pattern index, this study completed a stepwise multiple regression equation and correlation analysis to explore the relationship between the morphological structure and spatial configuration of GBS on the diffusion distance of atmospheric particles. The results show that the landscape shape index (LSI) and the number of patches (NP) of GBS have a significant positive correlation with the diffusion distance of atmospheric particles, while the coefficient of the percent of landscape (PLAND), as a key influencing factor, has a negative correlation. The mean Euclidean nearest neighbor distance (ENN_MN) and splitting index (SPLIT) in the spatial configuration metrics positively affect the diffusion distance. Studies have proved that complex and dispersed GBS will lead to the weakening of its purification ability, thereby increasing the pollution range of atmospheric particulate matter. The order of the influence of different GBS types on the diffusion distance of atmospheric particles is as follows: DT > BS > LP > ST > WA. Therefore, high-density GBS with simple shapes and concentrated distribution should be considered in the future construction of new cities.